Предмет: Алгебра,
автор: zem009
(3x-1) в3 степени =27х в 3 степени - 1
Ответы
Автор ответа:
0
Решение:
(3x-1)^3=27x^3-1
(3x-1)^3=(3x-1)*(9x^2+3x+1) разделим левую и правую части уравнения на (3х-1), получим:
(3x-1)^2=9x^2+3x+1
9x^2-6x+1=9x^2+3x+1
9x^2-6x+1-9x^2-3x-1=0
-9x=0
x=0:-9
х=0
Ответ: х=0
(3x-1)^3=27x^3-1
(3x-1)^3=(3x-1)*(9x^2+3x+1) разделим левую и правую части уравнения на (3х-1), получим:
(3x-1)^2=9x^2+3x+1
9x^2-6x+1=9x^2+3x+1
9x^2-6x+1-9x^2-3x-1=0
-9x=0
x=0:-9
х=0
Ответ: х=0
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Українська мова,
автор: dimoha2386
Предмет: Биология,
автор: Аноним
Предмет: Алгебра,
автор: skalargray
Предмет: Физика,
автор: senya1234511
Предмет: Алгебра,
автор: ekhard